(untitled) (Research, Society and Development, 2020)
The study aims to describe the consequences for the mental health of women victims of sexual violence, tracing the care received in the services of the Health Care Network. It is an integrative literature review, with a qualitative approach, carried out through the search of articles indexed in the Virtual Health Library (VHL), with the help of the following databases: Scientific Electronic Library Online (SCIELO), National Center for Biotechnology Information (PUBMED), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF), and Electronic Journals in Psychology (PEPSIC). The inclusion criteria include literature review surveys available in the databases described, between the years 2005 to 2020. As exclusion criteria, they were not considered articles for monetary reward, incomplete and not converging with this study. For data collection, 13 articles and 03 studies referring to health entities were analyzed. The results show the need for specialized monitoring of the mental health of women victims of sexual violence, given the drastic behavioral change after the act of violence. Consequently, resulting in depression, anxiety, use of anxiolytic drugs, trauma, fear, and social isolation, use of alcohol and drugs, worry, insomnia, panic attacks, suicide, among other factors. The study identified the importance of the perception of health professionals, for the identification of immediate cases, aiming to promote welcoming care practices, and a qualified perception to meet this demand, enabling the initial reception, integral, assistance and humanized monitoring.